CURRENT STATE OF INTERNATIONAL BEST PRACTICES IN SUPPORTING STUDENTS WITH DISABILITIES IN HIGHER EDUCATION INSTITUTIONS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Accessible pedagogy is a core focus within the spectrum of international best practices. Faculty and instructional designers are encouraged and, in many cases, required to employ principles of Universal Design for Learning (UDL) in curriculum development. UDL calls for flexible learning environments that anticipate different learning needs and offer multiple means of representation, expression, and engagement. Course materials are developed in accessible formats, digital platforms comply with accessibility standards, and assessment methods are adapted to recognize a variety of strengths and challenges. Training is provided to academic staff to enhance their competency in creating supportive learning settings.